COMPARISON BETWEEN AUTOREFRACTION AND RETINOSCOPY FOR SUBJECTIVE CORRECTION IN CHILDREN - YAR , MA; ZAHID , AH; NAWAB , R; RAO, MRQ; AADIL, N; HUSSAIN, S (Biological and Clinical Sciences Research Journal, 2023)
The study’s objective was to compare the accuracy of retinoscopy and autorefraction for subjective correction in children. The study was conducted in the Department of Ophthalmology at Nishtar Medical Hospital from June 2021 to May 2022, and it was a prospective study. The study included 60 children aged between 6 to 15 years who had asthenopic symptoms and blurring of vision. The children were given cyclopentolate 1% eyedrops thrice at intervals of 10 minutes to achieve cycloplegia. After an hour of instilling eye drops, cycloplegic retinoscopy, and autorefractometry were performed. Three values of each technique were recorded, and the average was calculated. After three days, binocular and monocular subjective refraction was performed until the best-corrected visual acuity (BCVA) was achieved. Results showed that 40.8% (49 eyes) were hypermetric, and 50% (60 eyes) were myopic based on subjective refraction. Comparison of spherical error by subjective refraction and retinoscopy showed that myopic eyes had a mean of -1.36 ± .98 and -1.08± .82 on subjective correction and retinoscopy, respectively (P=.07), and hypermetropic eyes had a mean of 2.5± .22 and 2.45± .22 on subjective correction and retinoscopy, respectively (P=0.07). Comparison of spherical error by subjective refraction and autorefractometer showed myopic eyes had a mean value of -1.51 ± 1.3 on autorefraction (P=.0001) while hypermetropic eyes had a mean of 2.39± .37 on autorefraction (P=0.0001). Mean cylindrical error values by retinoscopy were -.0729± .304, and by the subjective method, were -.167± .384 (P =0.0007). Mean cylindrical error values by autorefraction were .207± .487 compared to -.167± .384 by the subjective method (P =0.0088). In conclusion, conventional retinoscopy is the most accurate and reliable method for estimating the refractive status. However, autorefraction also has acceptable accuracy and can be used for cylindrical correction.